2017
DOI: 10.17503/agrivita.v39i2.949
|View full text |Cite
|
Sign up to set email alerts
|

Rice Root Distribution of Four Rice Varieties to Different Depth of Submergence

Abstract: Rice (Oryza sativa L

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Rice seeds of Ciherang variety were soaked in the water for 24 hours. Ciherang is widely grown rice variety in Indonesia (Nurrahma, Junaedi, Purnamawati, & Sakagami, 2017). Pre-germinated seeds were sown at a nursery plot applying samir system to produce rice seedlings.…”
Section: Methodsmentioning
confidence: 99%
“…Rice seeds of Ciherang variety were soaked in the water for 24 hours. Ciherang is widely grown rice variety in Indonesia (Nurrahma, Junaedi, Purnamawati, & Sakagami, 2017). Pre-germinated seeds were sown at a nursery plot applying samir system to produce rice seedlings.…”
Section: Methodsmentioning
confidence: 99%
“…Sub1A, a major quantitative trait locus (QTL) responsible for submergence tolerance, has been widely studied in FR13A rice (Oryza sativa L.) and is considered to confer submergence tolerance in rice breeding [11][12][13]. It has been introgressed into the high-yielding rice variety Inpari30 that did not result in any significant trait differences compared to the parental variety (Ciherang) under normal conditions [14][15][16]. Other studies reported the effect of submergence on shoot elongation in 15 genotypes of Oryza sativa under 80 cm water depth for 7 days.…”
Section: Introductionmentioning
confidence: 99%